Pengaruh Penggunaan Video Pembelajaran H5P Terhadap Hasil Belajar Siswa Pada Pembelajaran IPAS SD Kota Bengkulu - Azmi, Fadhil; Noperman, Feri (Universitas Bengkulu, 2026)
The purpose of this study is to ascertain how SDN Gugus 11th Bengkulu City's IPAS grade 4 learning outcomes are impacted by H5P learning video content. This kind of study uses quantitative methods. A quasi-experimental approach using the Matching Only Pretest-Posttest Kontrol Group Design is the study methodology employed. The study's participants were residents of Bengkulu City's SD Negeri Gugus 11th. This study used cluster random sampling to choose a sample of class 4thB SDN 44 Bengkulu City and class 4th SDN 55 Bengkulu City. A multiple-choice cognitive component learning outcome exam that was administered as a pretest and posttest served as the study toolThis study's data analysis methodology is quantitative and includes prerequisite test analysis, inferential analysis with t-test, and descriptive statistics. Based on the results of the inferential analysis, the t-count value (2.139) > t-table (1.674). The 2-tailed significance level is 0.037 <0.05. Including information on the experimental class's (70.00) and the kontrol class's (61.67) average scores in the scientific courses. The reason for the value difference is that the experimental group and the kontrol group received different treatments. While the kontrol group simply utilized oral questions and answers, the experimental group received instruction utilizing H5P-based video learning materials. These findings suggest that the utilization of H5P learning videos has an impact on the scientific learning outcomes of IPAS grade 4 students at SDN Gugus 11th in Bengkulu City.